Confluence of Disciplines in Health Informatics: an International Perspective - Geissbuhler, A.; Kimura, M.; Kulikowski, C. A.; Murray, P. J.; Ohno-Machado, L.; Park, H.-A.; Haux, R. (Methods of Information in Medicine, 2011)
Objective: To discuss international aspects as they relate to the convergence of disciplines in health informatics.Method: A group of international experts was invited at a symposium to present and discuss their perspectives on this topic. These have been collated in a single manuscript.Results and Conclusions: Significant challenges, as well as opportunities, appear when cumulating the intrinsic multidisciplinary nature of health informatics interventions with the diversity of contexts at the global level, in particular when considered in the perspective of a confluence, i.e., the mixing of different waters and their merging into a new, stronger entity. Health informatics experts reflect on key issues such as collaborative software development and distributed knowledge sourcing, social media and mobile technologies, the evolutions of the discipline from an historical perspective, as well as examples of challenges for implementing ubiquitous healthcare or for supporting disaster situations when infrastructures get disrupted.
Keywords: Biomedical informatics; health informatics; medical informatics; international perspectives; global health informatics